Indonesian Civil War: Comparing Discourse In the Campaign of Jakarta’s 2017 Gubernatorial Election - Muhammad Adek; Agustina Agustina (Fakultas Bahasa dan Seni UNP, 2021)
Political discourse today is no longer dependent on the performance of the political elite; however, it has shifted to active participation of their supporters. This phenomenon is widely recorded in social media as the background event. Without exception to Jakarta’s 2017 Gubernatorial Election that received an international spotlight because the roar is so massive in the universe of cyberspace. This qualitative descriptive study examined the pattern of campaign movements as a political discourse conducted by the public in supporters community account as a form of public participation in the politics of free-active democracy. It aimed to map out the pattern of discourse movements arising from the supporter community accounts of one of the candidate through the perspective of the discourse comparison offered by Sawirman (2014). The findings show that there are three supporting accounts of candidates which posited as primary, secondary and tertiary discourse. For the configuration of the discourse, gradable adjectives are used as a linguistic strategy to weaken and to dispel sympathy for opposing factions. It is based on the spirit that speakers are superior to their rivals. In general, the pattern of discourse movements identified is synergistic and mutual in order to demonstrate the superiority of their group by degrading the opposing side.